Strategi Dakwah Kampung Qur’an Dalam Meningkatkan Nilai-Nilai Religius Di Desa Kalidilem Randuagung Lumajang - Aang Burhanuddin; Zainil Ghulam (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2020)
Religious activities in the village of Kalidilem are already running but there are still some residents, especially teenagers, who get drunk and promiscuity. To overcome this problem a Kampung Qur’an program is formed. Kampung Qur'an is one of the Nahdlatul Ulama (NU, Islamic Organization) Lumajang programs that synergizes with JQH in the form of a missionary institution tasked with spreading the message of da'wah with the Qur'an. The village of the Qur'an was fully surrendered to the NU Autonomous Agency in charge of al-Qur'an. In the process of da'wah an important thing to consider is the da'wah strategy. This research uses descriptive qualitative method, with a phenomenological approach. Data collection techniques using interviews, observation and documentation. The conclusion of this study is the da'wah strategy used by the Qur'an Village there are 5 namely: 1) Sentimental strategy: conducting regular recitation, giving advice with good words, such as calling mad'u as "O my brothers, O my children" . 2) Rational strategy: invite people to discuss together. 3) Sensory Strategy: direct the practice of worship. 4) Ta'lim strategy: holding al-Qur'an illiteracy eradication program, development of tahfidzul quran, qiro'atul quran, art of calligraphy, organizing majlis of Qur'an interpretation and interpreneur of the Qur'an. 5) emulate the Prophet's strategy. The inhibiting factor of the preaching strategy of Kampung Qur'an is the lack of capable human resources in the field of al-Qur'an studies, understanding community psychology and having metacognitive abilities and philosophical thinking. Keywords: Da'wah strategy, religious values, Kampung Qur’an.